Inclusive Financing Through Microfinance - Pandey, Devendra Prasad (Indian Journal of Finance, 2008)
Microfinance in India: A State of the Sector Report, 2006", a report prepared by Prabhu Ghate and published by Microfinance India and jointly sponsored by Care, Ford Foundation and Swiss Agency for Development&Cooperation, says that ’microfinance in India has emerged as a powerful tool for financial inclusion, reaching out to a fifth of all poor households who have yet to be reached by the formal financial sector. The larger of the two main models, the self-help group bank linkage programme (SBLP) covered about 143 million poor households in March 2006 and provided indirect access to the banking system to another 14 million. The other, microfinance institution (MFI) model, served 7.3 million households, of which 3.2 million were poor.’ Apart from the scorching pace of growth, the report highlights several trends in Indian microfinance. First and, perhaps, most important, the rapid spread of microfinance has provided competition to rural money lenders. "ICICI Bank has catalyzed the creation of over 100 microfinance partners and has been able to extend micro-loans from 20000 clients in 2003 to 3 million clients by March, 2006. Microfinance has gained a lot of significance and momentum in the last decade. Indian model of microfinance offers greater promise and potential to address poverty as it is focused on building social capital through providing access to financial services through linking with the mainstream. Most of the microfinance institutions (MFIs) works towards promotion of community banking programme based on the principles of self help, mutuality and ownership by poor women.